Evidence of antibiotic resistance in Enterobacteriales isolated from green sea turtles, Chelonia mydas on the Great Barrier Reef. Issue 1 (15th July 2017) - Ahasan, Md. Shamim; Picard, Jacqueline; Elliott, Lisa; Kinobe, Robert; Owens, Leigh; Ariel, Ellen
Abstract: This study investigated Enterobacteriales and their antimicrobial resistance in green sea turtles captured adjacent to the central Great Barrier Reef (GBR) and proximate to urban development. Cloacal swabs were taken from 73 green turtles between 2015 and 2016. A total of 154 out of 341 Gram-negative bacterial isolates were identified as Enterobacteriales that represent 16 different species from 9 different genera. The dominant isolates were Citrobacter (30.52%), Edwardsiella (21.43%) and Escherichia (12.34%). The resistance against 12 antibiotics belonging to 6 different classes was determined. The isolates showed highest resistance to β-lactam antibiotics (78.57%) followed by quinolone (50%) and tetracycline classes (46.1%). Approximately one-third (37.7%) of the isolates identified exhibited multidrug-resistance. Isolates recovered from rehabilitated turtles were significantly multidrug resistant (p < 0.009) compared to isolates from other study sites. These results provide baseline information on antimicrobial resistance while revealing gaps for further research to evaluate the level of pollution in the GBR. Highlights: We reported evidence of microbial resistance to antibiotics in bacteria recovered from green turtles. Enterobacteriales strains were resistant to commonly used therapeutic antibiotics. 37.7% of the Enterobacteriales isolates were identified as multi-drug resistant. Multi-drug resistant isolates were more prevalent in stranded turtles in rehabilitation.